Towards surface wave tomography with 3D resolution and uncertainty: Resolution-uncertainty in 3D surface-wave tomography - Latallerie, Franck; Zaroli, Christophe; Lambotte, Sophie; Maggi, Alessia; Walker, Andrew; Koelemeijer, Paula (Seismica, 2025)
Surface-wave tomography is crucial for mapping upper-mantle structure in poorly instrumented regions such as the oceans. However, data sparsity and errors lead to tomographic models with complex resolution and uncertainty, which can impede meaningful physical interpretations. Accounting for the full 3D resolution and robustly estimating model uncertainty remains challenging in surface-wave tomography. Here, we propose an approach to provide direct control over the model resolution and uncertainty and to produce these in a fully three-dimensional framework by combining the Backus-Gilbert-based SOLA method with finite-frequency theory. Using a synthetic setup, we demonstrate the reliability of our approach and illustrate the artefacts arising in surface-wave tomography due to limited resolution. We also indicate how our synthetic setup enables us to discuss the theoretical model uncertainty (arising due to assumptions in the forward theory), which is often overlooked due to the difficulty in assessing it. We show that the theoretical uncertainty components may be much larger than the measurement uncertainty, thus dominating the overall uncertainty. Our study paves the way for more robust and quantitative interpretations in surface-wave tomography.